Korsaks private museum of the contemporary Ukrainian art: practice of cultural decentralization - S. P. Stoian, (Ukrainian Cultural Studies, 2018)
Culture is not an abstract concept, it is always created by individuals capable of changing the course of history and defining completely new vectors of social movement. And these vectors are not necessarily directed from the central, capital centers, as is commonly believed, according to current stereotypes, especially within the post-Soviet space.